DETEKSI RESPON ANTIBODI DAN FAKTOR RISIKO KEJADIAN INFEKSI VIRUS AI (INFLUENZA A/H5N1) PADA PEDAGANG UNGGAS DI PASAR TRADISIONAL KABUPATEN SUKOHARJO PROPINSI JAWA TENGAH - , Betty Indah Purnama; , Prof. drh. Setyawan Budiharta, MPH, Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The Sukoharjo District is an endemic area of Avian Influenza (H5N1). However, there are no reports stating traders of poultry infected with avian H5N1 virus. Therefore, serology investigation should be done to know the prevalence of AI virus infected (Influenza A/H5N1) on poultry traders in Sukoharjo traditional markets and to analyze the asociation of direct and indirect contact with the incidence of AI (Influenza A/H5N1) infection. Methods: The observational study was conducted with cross sectional design on 75 poultry traders from 8 traditional markets (sub-district) as the subjects. They were selected using simple random sampling proportionally. The dependent variable is the incidence of AI virus infection (Influenza A/H5N1) and the independent variables are direct contact with poultry and indirect contacts who were diagnosed H5N1 positive with the Hemagglutination Inhibition (HI) test. The descriptive used for statistical analysis. Results: Most of the subjects are women (74.7%), aged 41-60 years old (64.0%) and had elementary education (40.0%), the main job of poultry trade (69.3%), 6- 10 years of trading (33.3 %). The traders and poultry come from endemic areas in Sukoharjo District and neighboring districts. The highest risk factor of the AI virus infection incidence found on poultry traders by direct contact was washing carcasses (84.0%) and the lowest was contact with dead birds (28.0%), the highest by indirect contact were using the container carrier birds/carcasses and cleaning place of trading (94.7%). The lowest was washing hands after trading (86.7%). The anti-H5N1 antibody titer was negative (<40) in 75 subjects. Conclusion: The anti-H5N1 antibody titer were negative on poultry traders in the Sukoharjo traditional markets (prevalence 0%). That can be caused by the H5N1 virus is not easily transmitted from birds to humans whereas by frequent direct contact with suspected poultry, the differences of antigen that used for HI test with infective virus in Sukoharjo and virus antigenic changes in poultry. Percentage of direct contact risk factors found in this study were, in orderly fashion, washing carcass (84.0%), butchering poultry (80.0%), plucking feathears from poutry (77.3%), caring poutry (33.3%), contacting dead bird (28.0%), while for indirect one were using the container carrier birds/carcasses and cleaning place of trading 94.7%, washing hands after trading (86.7%). The Asociation between each of risk factors (direct and indirect contact) and infection of Avian Influenza virus (Influenza A/H5N1) in poultry traders could not be analyzed.